2013
DOI: 10.1111/cen.12373
|View full text |Cite
|
Sign up to set email alerts
|

How good is a morning cortisol in predicting an adequate response to intramuscular synacthen stimulation?

Abstract: Basal morning cortisol is a viable first step in the evaluation of patients with suspected adrenal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
3
41
1
Order By: Relevance
“…Moreover, in the Iran study, morning cortisol ≥6.2 μg/dL was defined as normal adrenal function. This cut‐off is low compared with a previous study that evaluated adrenal function after central nervous system insults (pituitary tumor, cranial radiation, and neurosurgery) and after insults due to other causes using morning cortisol cut‐offs 7.7 μg/dL (85% sensitivity, 71% specificity) and 8.5 μg/dL (84% sensitivity, 71% specificity), respectively . In the present study, the prevalenceof biochemical AI in ITT‐confirmed α‐thalassemia was 31%.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, in the Iran study, morning cortisol ≥6.2 μg/dL was defined as normal adrenal function. This cut‐off is low compared with a previous study that evaluated adrenal function after central nervous system insults (pituitary tumor, cranial radiation, and neurosurgery) and after insults due to other causes using morning cortisol cut‐offs 7.7 μg/dL (85% sensitivity, 71% specificity) and 8.5 μg/dL (84% sensitivity, 71% specificity), respectively . In the present study, the prevalenceof biochemical AI in ITT‐confirmed α‐thalassemia was 31%.…”
Section: Discussionmentioning
confidence: 51%
“…We have targeted 95% sensitivity in order to enable comparison with recently published literature. 6,7,17 Our data demonstrate NPV is very high using this threshold, although because of the dependence of NPV on pretest probability, caution is required in those with a particularly high index of clinical suspicion. Although setting a higher sensitivity would come at the expense of a greater proportion of patients requiring confirmatory testing, we found cut-offs of <308 and <312 nmol/L would achieve 99% and 100% sensitivity, respectively, for morning samples.…”
Section: Discussionmentioning
confidence: 71%
“…We have targeted 95% sensitivity in order to enable comparison with recently published literature . Our data demonstrate NPV is very high using this threshold, although because of the dependence of NPV on pretest probability, caution is required in those with a particularly high index of clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations